Executive Functioning of Sexually Compulsive and Non-Sexually Compulsive Men Before and After Watching an Erotic Video. Issue 3 (20th January 2017) - Messina, Bruna; Fuentes, Daniel; Tavares, Hermano; Abdo, Carmita H.N.; Scanavino, Marco de T.
Abstract: Introduction: Despite the serious behavioral consequences faced by individuals with sexual compulsivity, related neuropsychological studies are sparse. Aim: To compare decision making and cognitive flexibility at baseline and after exposure to an erotic video in sexually compulsive participants and non-sexually compulsive controls. Methods: The sample consisted of 30 sexually compulsive men and 30 controls. Cognitive flexibility was investigated through the Wisconsin Card Sorting Test and decision making was examined through the Iowa Gambling Task. Main Outcome Measures: Wisconsin Card Sorting Test categories, correct responses, and perseverative errors and Iowa Gambling Task general trends and blocks. Results: Sexually compulsive subjects and controls performed similarly at baseline. After watching an erotic video, controls performed better in block 1 of the Iowa Gambling Task ( P  = .01) and had more correct responses on the Wisconsin Card Sorting Test ( P  = .01). Conclusions: The controls presented fewer impulsive initial choices and better cognitive flexibility after exposure to erotic stimuli.